Pengamanan Acakan Biss Menggunakan Algoritma RSA - Indra Gunawan (STIKOM Tunas Bangsa Pematangsiantar, 2017)
BISS scramble method is a method in which description is done before the broadcast frequency signal sent to each TV station. This is done so that the delivery system and a broadcast signal receiving premium can be gated. BISS scramble method combined with RSA (Rivest Shamir Adleman), which later on safety in the delivery and receiving radio frequency signals broadcast video files can be gated and more robust against an attack.